PENGUATAN EKONOMI LOKAL MELALUI E-READINESS BERBASIS ONE VILLAGE ONE PRODUCT (OVOP) - Muafi Muafi; Titik Kusmantini; Hendri Gusaptono (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
This research aims to test; (1) the influences of organizational eReadiness to success of development, (2) the influences of external eReadiness to success of development, (3) the influences of organizational eReadiness to eCommerce benefit, (4) the influences of external eReadiness to eCommerce benefit, and (5) the influences of succces development to eCommerce benefit. Survey method is applied in this research. The data primary and secondary data. The population is the entire SME (small medium entreprises) in Jarum village, Bayat sub district, Klaten regency in Central Java. The sample quantity is 31 SME (small medium entreprises). The technique of sample drawing used is method of purposive sampling. This research applies statistical technique of Partial Least Square (PLS). The conclusion of all the hyphoteses proposed are; (1) there are no influences of organizational eReadiness to success of development, (2) there are influences of external eReadiness to success of development, (3) there are no influences of organizational eReadiness to eCommerce benefit, (4) there are influences of external eReadiness to eCommerce benefit, and (5) there are influences of succces development to eCommerce benefit.